AB0118 Oral contraceptives and the risk of developing rheumatoid arthritis: results from the malaysian epidemiological investigation of rheumatoid arthritis case-control study. (12th June 2018) - Too, C.L.; Nurul Aain, A.F.; Tan, L.K.; Lau, I.S.; Nor Asiah, M.L.; Salsabil, S.; Heselynn, H.; Nor Shuhaila, S.; Wahinuddin, S.; Gun, S.C.; Eashwary, B.; Mohd Shahrir, M.S.; et al.
Abstract : Background: Hormonal and reproductive factors are implicated in the etiology of rheumatoid arthritis (RA). The association between oral contraceptive (OC) use and the risk of RA has been reported, but the findings are inconsistent across different populations. Objectives: We investigated the association between OC use and risk of RA stratified by anti-citrullinated peptide antibody (ACPA) status in the Malaysian female population. Methods: Data from the Malaysian Epidemiological Investigation of rheumatoid Arthritis (MyEIRA) population-based case control study involving 902 female early RA and 906 age and residential area-matched female controls were analysed. OC use data was assessed through a questionnaire. Never users of OC were compared with ever users of OC to estimate the risk of developing ACPA-positive and ACPA negative RA. The odds ratio (OR) with 95% confidence interval (CI) was calculated. Results: In this study, a total of 28.4% (n=254) RA cases and 34.2% (n=310) controls had reported as ever OC users. Compared with never users, ever OC users had a decreased risk of developing RA in the Malaysian population particularly in ACPA-negative RA (OR 0.68, 95% CI 0.51–0.90, p<0.001). No significant association was observed between ever OC users and ACPA-positive RA (OR 0.80, 95% CI 0.64–1.01). Further stratification analysis by duration of OC use (less than or more than 7 years versus never OC use) demonstrated significant decreased risk of developing ACPA-positive RA (OR 0.66, 95% CI 0.51–0.86, p<0.01) and ACPA-negative RA (OR 0.57, 95% CI 0.41–0.80, p<0.001), respectively. Conclusions: Oral contraceptives decreased the risk of RA, particularly ACPA-negative RA in the Malaysian population. A long duration of OC use was however decreased the risk in both ACPA-positive and ACPA-negative RA subsets. References: [1] Orellano C, Saevardottir S, Klareskog L, Karlson EW, Alfredsson L, Bengtsson C. Oral contraceptives, breastfeeding and the risk of developing rheumatoid arthritis: results from the Swedish Epidemiological Investigation of Rheumatoid Arthritis study. Ann Rheum Dis. 2017;76:1845–1852. [2] Adab P, Jiang CQ, Rankin E, Tsang YW, Lam TH, Barlow J, Thomas GN, Zhang WS and Cheng KK. Breastfeeding practice, oral contraceptive use and risk of rheumatoid arthritis among Chinese women: the Guangzhou Biobank Cohort Study. Rheumatology (Oxford)2014;53(5):860–6. Disclosure of Interest: None declared